Cover Picture: Elucidating Inorganic Nanoscale Species in Solution: Complementary and Corroborative Approaches (ChemPhysChem 12/2013). Issue 12 (19th August 2013) - Oliveri, Anna F.; Elliott, Edward W.; Carnes, Matthew E.; Hutchison, James E.; Johnson, Darren W.
<x xml:space="preserve">Abstract</x> Size measurements can describe a number of different dimensions for a well‐defined inorganic nanoscale species (core, shell, solvation sphere). Since many of the techniques used to measure size depend on significant and sometimes destructive sample preparations, an additional challenge is defining what size means for a nanoscale species in solution. Techniques such as SAXS, DOSY, and DLS are ideal for determining these dimensions in solution. J. E. Hutchison, D. W. Johnson et al. illustrate on p. 2655 complementary techniques that can be used together to unveil more information about the material in question. The pictured corroborative techniques can make multiple measurements of the same property.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>